The Journeys of Muhammad and the Mountain: the Concept of Displacement in Karl Bühler and Rafael Sánchez Ferlosio - Santana Pérez, Sandra (Revista de Filosofía, 2019)
Rafael Sánchez Ferlosio used the concept of «displacement», taken from the work of the German psychologist Karl Bühler, to analyze the important role of metaphor in the development of human language. The purpose of this article is to provide a comparative and complementary reading of the different meanings of this concept for both authors, as well as consider the philosophical implications.
Keywords: theory of language; philosophy of language; metaphor; psychology; linguistic.